N1 and P2 to words and wordlike stimuli in late elementary school children and adults. (16th October 2015) - Coch, Donna; Meade, Gabriela
Abstract: In an investigation of the development of fine‐tuning for word processing across the late elementary school years as indexed by the posterior N1 and P2 components of the ERP waveform, third, fourth, and fifth graders and a comparison group of adults viewed words, pseudowords, nonpronounceable letter strings, and false font strings in a semantic categorization task. In adults, N1 was larger to and P2 was later to words as compared to pseudowords, a finely tuned effect of lexicality reflecting specialization for word processing. In contrast, in each group of children, N1 was larger to letter strings than false font strings and P2 was larger to false font strings than letter strings, reflecting coarse encoding for orthography. In regression analyses, scores on standardized behavioral test measures of orthographic knowledge, decoding skill, and fluency predicted N1 amplitude; these effects were not significant with age included as a separate predictor. None of the behavioral scores, in models including or not including age, predicted P2 amplitude. In direct comparisons between groups, there were multiple differences between the child and adult groups for both N1 and P2 amplitude effects, and only a single significant difference between two child groups. Overall, the findings suggest a lengthy developmental time course for the fine‐tuning of early word processing as indexed by N1 and P2.